Gastrin attenuates ischemia-reperfusion-induced intestinal injury in rats. Issue 8 (April 2016) - Liu, Zhihao; Luo, Yongli; Cheng, Yunjiu; Zou, Dezhi; Zeng, Aihong; Yang, Chunhua; Xu, Jia; Zhan, Hong
Intestinal ischemia-reperfusion (I/R) injury is a devastating complication when the blood supply is reflowed in ischemic organs. Gastrin has critical function in regulating acid secretion, proliferation, and differentiation in the gastric mucosa. We aimed to determine whether gastrin has an effect on intestinal I/R damage. Intestinal I/R injury was induced by 60-min occlusion of the superior mesenteric artery followed by 60-min reperfusion, and the rats were induced to be hypergastrinemic by pretreated with omeprazole or directly injected with gastrin. Some hypergastrinemic rats were injected with cholecystokinin-2 (CCK-2) receptor antagonist prior to I/R operation. After the animal surgery, the intestine was collected for histological analysis. Isolated intestinal epithelial cells or crypts were harvested for RNA and protein analysis. CCK-2 receptor expression, intestinal mucosal damage, cell apoptosis, and apoptotic protein caspase-3 activity were measured. We found that high gastrin in serum significantly reduced intestinal hemorrhage, alleviated extensive epithelial disruption, decreased disintegration of lamina propria, downregulated myeloperoxidase activity, tumor necrosis factor-α, and caspase-3 activity, and lead to low mortality in response to I/R injury. On the contrary, CCK-2 receptor antagonist L365260 could markedly impair intestinal protection by gastrin on intestinal I/R. Severe edema of mucosal villi with severe intestinal crypt injury and numerous intestinal villi disintegrated were observed again in the hypergastrinemic rats with L365260. The survival in the hypergastrinemic rats after intestinal I/R injury was shortened by L365260. Finally, gastrin could remarkably upregulated intestinal CCK-2 receptor expression. Our data suggest that gastrin by omeprazole remarkably attenuated I/R induced intestinal injury by enhancing CCK-2 receptor expression and gastrin could be a potential mitigator for intestinal I/R damage in the clinical setting.